Market integration and natural resource use in developing countries: a linked agrarian-resource economy in Northern Honduras. (April 2014) - Manning, Dale T.; Taylor, J. Edward; Wilen, James E.
Abstract Most resource management studies model the resource in isolation from the rest of the economy of which it is part. In many developing economies, agents participate in multiple activities, creating linkages between resource exploitation and other sectors (e.g., agriculture). In Northern Honduran fishing communities, households allocate effort to fishing according to the opportunity cost of their time, which depends on returns in other activities. We develop a model that demonstrates how market structure impacts fishery exploitation. Agricultural price increases have an ambiguous effect on labor allocated to fishing because they reduce the value of labor in fishing but increase the demand for fish via an income effect. The size and magnitude of impacts depend strongly on the tradability of inputs and outputs in the community economy. The findings point to a need to account for economic linkages and market structure when designing policies to reduce pressure on a natural resource.